THE ROLE OF MANAGEMENT CONSULTING IN THE EDUCATIONAL PROCESS - BILYK, Victoriia; DESIATOV, Tymofii; KARAMSHCHUK, Anna (Herald of Khmelnytskyi National University. Economic sciences, 2025)
The relevance of the research topic is determined by the growing need of educational institutions to implement modern management technologies that enhance the efficiency of the educational process, optimize managerial decision-making, and ensure institutional competitiveness. In the context of educational reform in Ukraine, integration into the European educational space, and the expansion of university autonomy, management consulting emerges as an important tool of professional support for educational leaders. It contributes to the development of strategic thinking, improvement of human resource policies, formation of an innovative environment, and overall enhancement of educational quality. Thus, the study of the role of management consulting in education has both theoretical and practical significance, as it allows the identification of effective mechanisms for adapting managerial decisions to contemporary challenges.The modern educational system is undergoing constant transformations driven by globalization, digitalization, and evolving management approaches. Leaders of educational institutions face the necessity of making strategically sound decisions, which requires not only pedagogical expertise but also advanced managerial competence. However, the potential of management consulting as a support instrument is still underutilized in practice, which lowers the effectiveness of educational processes. This underlines the need for systematic scientific research into its role in educational management.An analysis of recent studies (conducted by V. Bykov, O. Spirin, S. Lytvynova, O. Derevyanko, N. Bobro, S. Kozmenko, O. Kuzmin, as well as M. Ferguson, F. Cherniavska, T. Ambuster, A. Daniel, A. Grossa, S. Kanbaka, and others) shows that the issue of management consulting in education has been actively explored. Nevertheless, it requires further elaboration, particularly in the context of applying consulting practices to the specific needs of educational institutions.The aim of the study is to define the essence and role of management consulting in the educational process and to develop practical recommendations for its effective implementation in educational institutions. The research objectives include analyzing the theoretical foundations of consulting, identifying the specifics of applying consulting practices in education, assessing their impact on the quality of the educational process and managerial decisions, and outlining strategies for further improvement.The findings confirm that management consulting serves as a significant mechanism for enhancing managerial competence, optimizing organizational processes, fostering innovation, and supporting institutional development. It provides a comprehensive analysis of educational activities, identifies existing challenges, and formulates scientifically grounded recommendations that contribute to more effective governance. The conclusions highlight that management consulting in education is a key tool for strengthening strategic development, resource optimization, institutional competitiveness, and the formation of a culture of effective management. Its implementation helps educational institutions increase productivity, support innovative practices, and create a favorable environment for sustainable growth in the educational sector.
Keywords: management consulting; educational process; educational management; management efficiency; consulting technologies; strategic management; innovative development of education